Perhitungan Rem Cakram Roda Depan Motor Revo Absolute 110cc Tahun 2010 - Karna Haerudin; Kardiman Kardiman; Aripin Aripin (Jurnal Ilmiah Wahana Pendidikan, 2022)
The development of science and technology is experiencing very rapid growth. Since the birth of the industrial revolution with the invention of steam engines, otto engines and human diesel engines have been competing to conduct research to find technology that aims to facilitate daily human activities, without exception, technological developments in the automotive field have been progressing very rapidly. The purpose of this study is to determine the magnitude of the braking force, the magnitude of the pressure force of the brake pads and the life of the disc brake pads at a certain codition. Based on the results of the calculations that have been carried out, the force transmitted in each braking process is 62,911 Kgf, the piston pressing force is 265,666 Kgf and the piston pressure force is 21 Kgf. Then for the brake pad age, which is 994.28 hours.